A NEW VERSION OF POST COVID TOURISM (International Journal of Food and Nutritional Sciences, 2023)
Tourism has played a significant role in economic development of regions across the world. Creating jobs, encouraging local arts and crafts, building infrastructure and improving amenities are some of its key roles. The outbreak of the COVID-19 pandemic imposed severe restrictions on travel and tourism, reversing the spectacular growth registered by the industry in the preceding years. The urgent need of the hour is to take short and long-term measures to overcome the present slowdown in the tourism industry by reviewing its impacts. This study was conducted with 100 respondents to understand the perceptions, behaviour and fears of tourists. The data was collected through google doc and secondary sources from newspapers, reports etc. The methodology includes the use of statistical method to show the age of respondents, destination etc. The Chi Square has been used to calculate the relationship between various variables. It reveals a preference of tourists to stay in safety bubbles while traveling to destinations chosen on the basis of easy accessibility, availability of online booking facilities, and availability of internet connectivity. They were by and large satisfied with safety measures adopted in places of stay although they were scared by non-compliance of safety protocols by fellow travellers and public at large. The pandemic has seen the emergence of new forms of tourism. These include revenge tourism – by people who are anxiously trying to overcome their ‘lockdown fatigue’, Phila tourism, a portmanteau of philanthropy and tourism and workcation- working remotely from a tourist destination rather than from home.